Dissecting Common and Unique Effects of Anti-α4β7 and Anti-Tumor Necrosis Factor Treatment in Ulcerative Colitis. (14th September 2020) - Veny, Marisol; Garrido-Trigo, Alba; Corraliza, Ana M; Masamunt, Maria C; Bassolas-Molina, Helena; Esteller, Miriam; Arroyes, Montserrat; Tristán, Eva; Fernández-Clotet, Agnès; Ordás, Ingrid; Ricart, Elena; Esteve, Maria; et al.
Abstract: Background and Aims: Vedolizumab is an anti-α4β7 antibody approved for the treatment of ulcerative colitis [UC]. Although it is assumed that vedolizumab blocks intestinal homing of lymphocytes, its effects on different intestinal cell populations are not fully stablished. In order to establish the unique mechanisms of action of vedolizumab in UC patients, we compared its effects to those induced by anti-tumour necrosis factor [TNF]. Methods: Patients with active UC [endoscopic Mayo score >1] starting vedolizumab [ n = 33] or anti-TNF [ n = 45] and controls [ n = 22] were included. Colon biopsies [at weeks 0, 14 and 46] and blood samples [at weeks 0, 2, 6, 14, 30 and 46] were used for cell phenotyping, transcriptional analysis [qPCR], and to measure receptor occupancy. Results: Vedolizumab, in contrast to anti-TNF, significantly reduced the proportion of α4β7 + cells within intestinal T subsets while preserving the percentage of α4β7 + plasma cells. The marked decrease in α4β7 did not change the percentage of colonic αEβ7 + cells [at 46 weeks]. Both vedolizumab and anti-TNF significantly downregulated inflammation-related genes in the colon of responders [Mayo score < 2]. Moreover, both treatments significantly decreased the percentage of intestinal, but not blood, total lymphocytes [T and plasma cells], as well as the proportion of α4β1 + cells within intestinal T lymphocytes. Conclusions: Our data show that while vedolizumab and anti-TNF block two unrelated targets, they induce remarkably similar effects. On the other hand, vedolizumab's unique mechanism of action relies on blocking intestinal trafficking of α4β7 T cells, despite effectively binding to B and plasma cells that express α4β7.